IM Effectiveness and Reliability to Employee's Performance in Universities in Pekanbaru - Hartati, Seri; Arisandi, Diki; Rahmalina, Widdya (Jurnal Manajemen Teknologi, 2019)
Abstract. In educational institutions such as universities, use of the smartphones, especially the Instant Messaging (IM) application, allowing employees, including lecturers are able to communicate and share the information anytime and anywhere. This research discussed how IM effectiveness and reliability in increasing employee's performance. The used outcome regression analysis indicated that based on IM effectiveness and reliability, employee's performance increased by using IM assistance in their working activities. The outcome is expected to provide an overview and understanding of the importance in using technology such as IM in increasing employee performance in universities in Pekanbaru.Keywords: Instant messaging, effectiveness, universities, employee, performance.Abstrak. Pada lembaga pendidikan seperti Universitas, penggunaan smartphone terutama aplikasi Instant Messanging (IM) memungkinkan antar karyawan, termasuk dosen untuk dapat berkomunikasi dan berbagi informasi kapan saja dan di mana saja. Dalam penelitian ini dibahas bagaimana efektivitas dan kehandalan IM dalam meningkatkan kinerja karyawan. Hasil analisis regresi yang digunakan menunjukkan bahwa berdasarkan efektifitas dan kehandalan IM, kinerja karyawan mengalami peningkatan dengan menggunakan bantuan IM dalam bekerja. Hasil penelitian ini diharapkan dapat memberikan gambaran dan pemahaman akan pentingnya penggunaan teknologi seperti IM dalam meningkatkan kinerja karyawan pada Universitas di Pekanbaru.Kata kunci: Pesan instan, keefektifan, universitas, karyawan, kinerja.